2014
DOI: 10.1016/j.crci.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sulfate and nitrate uptake from aqueous solutions on surface exchange in Purolite A-520E resin

Abstract: Removal of nitrate anions from aqueous solutions is the principal goal of many studies concerning water treatment. The ion exchanger capacity to remove nitrate from water was investigated using commercial type A-520E anion exchange resins. The nitrate and sulfate ion exchanger capacity, in static conditions, depends on the concentration of ions and on the pH value of the aqueous solution. The local structural environment exchanged on A-520E has been investigated by scanning electron microscopy (SEM), energy-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It was determined that an increase in the pH value in the range of 3.9 to 8.2 caused a decrease in the sorption capacity for nitrate and sulfate ions from the aqueous solution. Therefore, they observed that polymer a-520e is very good for removing nitrate anions from aqueous solutions due to its high selectivity towards nitrate ions (Stefan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that an increase in the pH value in the range of 3.9 to 8.2 caused a decrease in the sorption capacity for nitrate and sulfate ions from the aqueous solution. Therefore, they observed that polymer a-520e is very good for removing nitrate anions from aqueous solutions due to its high selectivity towards nitrate ions (Stefan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…No reports have been found about nitrite removal using monometallic catalysts supported on anionic resins. On the other hand, the effect of competing ions such as sulfates, chlorides and bicarbonates on the exchange capacity and catalytic activity of the resins, were addressed only in few studies [20][21][22][23], in spite of being a key issue in order to properly determine the real catalytic behavior [24].…”
Section: Introductionmentioning
confidence: 99%
“…Upon exposure to oxidizing conditions some sulphide minerals are oxidized in the presence of water and oxygen to form highly acidic, sulphate-rich wastewaters. Acidity levels, and metal composition and concentration depend on the type and amount of sulphide mineral and the presence or absence of alkaline materials [2,3]. Iron sulphides common in coal regions are predominately pyrite and marcasite (FeS 2 ), but other metals may be combined with sulphide in the form of chalcopyrite (CuFeS 2 ), covellite (CuS), and arsenopyrite (FeAsS) [4].…”
Section: Introductionmentioning
confidence: 99%